2018
DOI: 10.1152/ajpcell.00328.2017
|View full text |Cite
|
Sign up to set email alerts
|

Dextran sulfate sodium-induced chronic colitis attenuates Ca2+-activated Cl secretion in murine colon by downregulating TMEM16A

Abstract: Attenuated Ca-activated Cl secretion has previously been observed in the model of dextran sulfate sodium (DSS)-induced colitis. Prior studies have implicated dysfunctional muscarinic signaling from basolateral membranes as the potential perpetrator leading to decreased Ca-activated Cl secretion. However, in our chronic model of DSS-colitis, cholinergic receptor muscarinic 3 ( Chrm3) transcript (1.028 ± 0.12 vs. 1.029 ± 0.27, P > 0.05) and CHRM3 protein expression (1.021 ± 0.24 vs. 0.928 ± 0.09, P > 0.05) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
5
8
0
Order By: Relevance
“…Experiments in the Tmem16a -/- mouse pups have shown that there is a reduction in the intestinal Ca 2+ -dependent chloride secretion (Ousingsawat et al, 2009). Similar results were observed when Tmem16a was specifically silenced from the intestinal epithelium of adult mice (Schreiber et al, 2015) and, more recently, calcium-activated chloride secretion has been reported to be decreased concomitantly to TMEM16A expression in mouse colon (Rottgen et al, 2018). Nevertheless, we and others have determined that both cAMP and Ca +2 -activated chloride secretion are occurring via CFTR exclusively in both human and mouse intestine (Seidler et al, 1997; Mall et al, 2000a,b; Zdebik et al, 2004; Bijvelds et al, 2009; Flores et al, 2009; Philp et al, 2018).…”
Section: Introductionsupporting
confidence: 77%
“…Experiments in the Tmem16a -/- mouse pups have shown that there is a reduction in the intestinal Ca 2+ -dependent chloride secretion (Ousingsawat et al, 2009). Similar results were observed when Tmem16a was specifically silenced from the intestinal epithelium of adult mice (Schreiber et al, 2015) and, more recently, calcium-activated chloride secretion has been reported to be decreased concomitantly to TMEM16A expression in mouse colon (Rottgen et al, 2018). Nevertheless, we and others have determined that both cAMP and Ca +2 -activated chloride secretion are occurring via CFTR exclusively in both human and mouse intestine (Seidler et al, 1997; Mall et al, 2000a,b; Zdebik et al, 2004; Bijvelds et al, 2009; Flores et al, 2009; Philp et al, 2018).…”
Section: Introductionsupporting
confidence: 77%
“…We therefore measured short circuit current (I SC ) across pieces of distal colon stripped of smooth muscle after equilibrating the tissues for 30 min in symmetrical Krebs solution. Similar to previously reported values for basal I SC of mouse distal colonic mucosae (30, 47, 48), our WT tissues showed on average a basal I SC = 21.6 ± 10.0 μA/cm 2 (mean ± SD, n=10) (Fig. 4A-B, E).…”
Section: Resultssupporting
confidence: 91%
“…Dysfunction of Cl − secretion has been observed in intestinal inflammation, and TMEM16A has been identified as the primary mediator of Ca 2+ -activated Cl − secretion in the colonic epithelium 43,44 . TMEM16A protein levels were decreased in a DSS-induced colitis model, and the authors predicted that the colitis was caused by downregulation of TMEM16A due to the stimulation of Th2 cytokines by DSS 45 . However, the mechanism responsible for mediating the downregulation of TMEM16A is unclear.…”
Section: Discussionmentioning
confidence: 99%